Risk factors for recurrence of primary sclerosing cholangitis in pediatric liver transplant recipients: A meta-analysis - Sun, Bei; Guan, Dong; Gao, Yu-Geng; Chen, Jing-Yi; Rong, Yi-Hui; Guo, Zuo-Ming (World journal of gastrointestinal surgery, 2025)
Risk factors for recurrence of primary sclerosing cholangitis in pediatric liver transplant recipients: A meta-analysis
Gesehen am 22.10.2025